Entrepreneurial Leadership and Gender: Exploring Theory and Practice in Global Contexts. (21st April 2015) - Henry, Colette; Foss, Lene; Fayolle, Alain; Walker, Elizabeth; Duffy, Susan; Henry, Colette; Foss, Lene; Fayolle, Alain; Walker, Elizabeth; Duffy, Susan
<x xml:space="preserve">Abstract</x> This article reflects on extant scholarship on entrepreneurial leadership and gender, as published in both the Journal of Small Business Management and elsewhere. As such, it lays the foundation for the special issue, and contributes to current knowledge in the field. Our selected papers—summarized and critiqued in this article—collectively offer a contemporary view of women's entrepreneurial leadership at the global level that should usefully contribute to extending scholarly debates. In this regard, we highlight the diversity and complexity of women's entrepreneurial leadership, and demonstrate that it is both economically and contextually embedded, worthy of further scholarly attention.